Biodegradation of polyaromatic hydrocarbons by recombinant bacteria containing Alasan gene. (21st July 2009) - Ahmed, M.M.M.; Hafez, Elsayed E.; El-Saadani, M.A.
Alasan, the bioemulsifier of Acinetobacter radioresistens KA53, is a high molecular-mass complex of an alanine-containing polysaccharide and three proteins. This gene was isolated from the A. radioresistens using PCR and the amplified product (850 bp) was cloned using PGEMT cloning kit. DNA sequence was carried out for the amplification and sequence analysis showed that the PCR product was highly similar to the OMPA precursor protein which called Alan. Subcloning was carried out into pTRAC expression vector and the purified protein was used in mineralisation of the polyaromatic hydrocarbon. As well as the recombinant E. coli cells were cultured directly on MSM containing four polyaromatic hydrocarbon using real time method (phenol, naphthalene, phenantherene and antherathene). The obtained results showed that no difference between the purified protein and the using of the recombinant cells directly with the presence of the inducer like IPTG. Both of the purified protein and the recombinant cells showed high degradation rates for (anthrathene and phenantherene).